Superrepellent Doubly Reentrant Geometry Promotes Antibiofouling and Prevention of Coronavirus Contamination. Issue 1 (5th August 2022) - Lee, Meng‐Shiue; Chien, Yueh; Teng, Pai‐Chi; Huang, Xuan‐Yang; Lin, Yi‐Ying; Lin, Ting‐Yi; Chou, Shih‐Jie; Chien, Chian‐Shiu; Hsiao, Yu‐Jer; Yang, Yi‐Ping; Hsu, Wensyang; Chiou, Shih‐Hwa
Abstract: The fomite transmission of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has drawn attention because of its highly contagious nature. Therefore, surfaces that can prevent coronavirus contamination are an urgent and unmet need during the coronavirus disease 2019 (COVID‐19) pandemic. Conventional surfaces are usually based on superhydrophobic or antiviral coatings. However, these coatings may be dysfunctional because of biofouling, which is the undesired adhesion of biomolecules. A superhydrophobic surface independent of the material content and coating agents may serve the purpose of antibiofouling and preventing viral transmission. Doubly reentrant topology (DRT) is a unique structure that can meet the need. This study demonstrates that the DRT surfaces possess a striking antibiofouling effect that can prevent viral contamination. This effect still exists even if the DRT surface is made of a hydrophilic material such as silicon oxide and copper. To the best of our knowledge, this work first demonstrates that fomite transmission of viruses may be prevented by minimizing the contact area between pathogens and surfaces even made of hydrophilic materials. Furthermore, the DRT geometry per se features excellent antibiofouling ability, which may shed light on the applications of pathogen elimination in alleviating the COVID‐19 pandemic. Abstract : The findings demonstrate that a unique fabricated doubly reentrant topology (DRT) structure carries remarkable superrepellent properties against biofouling of protein, blood, bacteria, and viruses. Moreover, this characteristic results from a highly minimized contact area and still exists even if the DRT surface is made of a hydrophilic material, such as silicon oxide.